Converting rejections into positive stimuli (Past, Present, and Future of Statistical Science, 2014)
At first glance this Einstein quotation may seem to have little to do with my title, but those readers who know something of Einstein’s early life will recall that these years were not full of recognized scientific successes, but he kept working on his problems. And that is certainly related to why I chose the quote, but there is more to it. I have been fortunate to have had many journal publications, but less than one percent were accepted at first submission — far more were immediately rejected, followed closely by those that were rejected accompanied with the suggestion that it would not be wise to resubmit. However, I cannot think of an instance where this nasty treatment of my magnificent (self-assessed) work (sometimes joint) did not lead to a markedly improved publication, somewhere. In fact, I think that the drafts that have been repeatedly rejected by many different journals possibly represent my best contributions! Certainly the repeated rejections, combined with my trying to address various comments, led to better exposition and sometimes better problem formulation as well.